Pengaruh Driver’s Savings Terhadap Net Income PT Blue Bird Tbk Periode 2015-2024 (Mengecualikan Periode COVID-19) - Andra Prabowo , Chaidir; Tarida Geraldine, Keisha; Manurung, Elizabeth Tiur (Politeknik Negeri Jakarta, 2025)
This study investigates the impact of driver’s savings on the net income of PT Blue Bird Tbk for the period 2015–2024, excluding the COVID-19 pandemic period. Utilizing a quantitative approach, the study relies on secondary data from the company’s financial reports. Data analysis was conducted using a simple linear regression model after applying natural logarithmic transformation. The results indicate that driver’s savings have no significant influence on the company's net income, as evidenced by a significance value exceeding 5%. This suggests that the relatively small amount of driver’s savings does not substantially contribute to financial performance. Future researchers are encouraged to explore additional variables, such as employee turnover rates, to deepen the understanding of how employee saving programs impact corporate financial outcomes.) Keywords: Driver’s Savings; Net Income